2022
DOI: 10.3390/molecules27123911
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Targeted Therapy of Pediatric Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) accounts for approximately 15–20% of all childhood leukemia cases. The overall survival of children with acute myeloid leukemia does not exceed 82%, and the 5-year event-free survival rates range from 46% to 69%. Such suboptimal outcomes are the result of numerous mutations and epigenetic changes occurring in this disease that adversely affect the susceptibility to treatment and relapse rate. We describe various molecular-targeted therapies that have been developed in recent years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
0
8
0
1
Order By: Relevance
“…Rhabdomyosarcoma is the most frequent sarcoma in children, but neuroblastoma, ES, and osteosarcoma are also common [7]. In haematological malignancies the use of venetoclax is already ongoing in clinical trials for relapsed, refractory or high-risk leukaemia [87,88]. Based on the previous findings in ES, a study in 2020 by Kehr et al [89] demonstrated that rhabdomyosarcoma, osteosarcoma, and neuroblastoma cell lines were co-dependent of Bcl-xL and MCL-1 for survival.…”
Section: Pediatric Sarcomasmentioning
confidence: 99%
“…Rhabdomyosarcoma is the most frequent sarcoma in children, but neuroblastoma, ES, and osteosarcoma are also common [7]. In haematological malignancies the use of venetoclax is already ongoing in clinical trials for relapsed, refractory or high-risk leukaemia [87,88]. Based on the previous findings in ES, a study in 2020 by Kehr et al [89] demonstrated that rhabdomyosarcoma, osteosarcoma, and neuroblastoma cell lines were co-dependent of Bcl-xL and MCL-1 for survival.…”
Section: Pediatric Sarcomasmentioning
confidence: 99%
“…With current therapeutic regimens, over 50% of AML patients will relapse within 1 year, and 80% of AML patients will relapse within 5 years. [ 2 ] Therefore, research is necessary to better understand the molecular mechanisms of the initiation and progression of AML and to develop novel therapeutic approaches for AML patients, particularly for relapsed patients with a much poorer prognosis. In addition, potent drugs for the specific treatment of age-related leukemia remain undeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…AML often presents with fever, anemia, hemorrhage, lymphadenopathy, and hepatosplenomegaly. [1] In the past 20 to 30 years, the survival rate of childhood AML has improved significantly, with an overall survival rate of 60% to 70%, and an event-free survival rate of over 50%. [2][3][4][5][6][7] Due to the prothrombotic nature of cancer and its associated coagulopathies as well as the use of chemotherapeutic agents, the use of central venous catheters, surgery, and radiotherapy, children with cancer tend to have increased risks of thromboembolism (TE).…”
Section: Introductionmentioning
confidence: 99%